Pengaruh Jumlah Penduduk, Pengangguran, Dan Pendidikan Terhadap Kemiskinan Di Provinsi Jawa Timur - Emilia Titah Nabibah; Nurul Hanifa (Universitas Negeri Surabaya, 2022)
This study tries to find out how education, unemployment, and population influence poverty in East Java province. This information is taken from BPS publications for 2018–2021. The panel data regression analysis of this study resulted in the finding that poverty (KM) is not affected by a portion of the population (JP). Poverty (KM) is significantly increased by unemployment (PG). Poverty is significantly influenced by education (KM). While population, unemployment, and education all work together to affect poverty. Keywords: Poverty, Total Population, Unemployment, Education